2021
DOI: 10.46557/001c.27015
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamics of Oil Prices, Exchange Rates, and the Stock Market Under COVID-19 Uncertainty: Evidence From India

Abstract: This study empirically analyzes the dynamic relation between oil price returns, exchange rates, stock returns, and uncertainty shocks. Utilizing daily data, we employ a structural vector autoregression econometric technique to explore the impact of uncertainty in the Indian context. The study finds that COVID-19-induced uncertainty dampened the oil and stock markets. Further, findings suggest that COVID-19-induced uncertainty distorted the dynamics between oil and stock prices in the initial periods, due to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 13 publications
7
20
0
Order By: Relevance
“…Our results are consistent with the findings documented in Thorbecke (2021) , Narayan et al (2020) , Camba and Camba (2020) , Aslam et al (2020) , Syahri and Robiyanto (2020) , Hoshikawa and Yoshimi (2021) , Prabheesh and Kumar (2021) , Amewu et al (2022) , Narayan (2022) . For example, Syahri and Robiyanto (2020) found significant relationship between exchange rate and composite stock price index during the coronavirus era; Aslam et al (2020) confirmed that the efficiency of the foreign exchange market for six major global currencies declined during the earlier part of the COVID-19 pandemic; Narayan et al (2020) recorded significant dynamic correlation between the Japanese Yen and the stock market returns, as the Yen depreciated against the US dollar, the returns on stock market improved in Japan.…”
Section: Empirical Results and Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…Our results are consistent with the findings documented in Thorbecke (2021) , Narayan et al (2020) , Camba and Camba (2020) , Aslam et al (2020) , Syahri and Robiyanto (2020) , Hoshikawa and Yoshimi (2021) , Prabheesh and Kumar (2021) , Amewu et al (2022) , Narayan (2022) . For example, Syahri and Robiyanto (2020) found significant relationship between exchange rate and composite stock price index during the coronavirus era; Aslam et al (2020) confirmed that the efficiency of the foreign exchange market for six major global currencies declined during the earlier part of the COVID-19 pandemic; Narayan et al (2020) recorded significant dynamic correlation between the Japanese Yen and the stock market returns, as the Yen depreciated against the US dollar, the returns on stock market improved in Japan.…”
Section: Empirical Results and Discussionsupporting
confidence: 94%
“…This shows that changes in exchange rates in these net-oil producing economies appear to negatively affect their stock markets, i.e., exchange rates appear to deteriorate stock markets performances in this economies. The result is consistent with the findings of Basher et al (2012) , Kumar (2019) , Narayan (2020) , Syahri and Robiyanto (2020) , Aslam et al (2020) , Prabheesh and Kumar (2021) . For example, Narayan (2020) found a significant effect of the uncertainty caused by COVID-19 on the Japanese Yen and argued that the currency market was non-stationary in the pre-COVID-19, but become stationary during the COVID-19 period.…”
Section: Empirical Results and Discussionsupporting
confidence: 92%
See 3 more Smart Citations